Comparison of low urinary tract symptoms during pregnancy between primiparous and multiparous women after vaginal delivery versus caesarean section - N A Osipova; D A Niaury; A M Gzgzyan; G M Ziyatdinova (IP Berlin A.V., 2015)
Low urinary tract symptoms (LUTS) are a common problem during pregnancy. This study aimed to compare changes in the prevalence of LUTS during pregnancy between primiparous and multiparous women after vaginal delivery versus caesarean section.In total 270 women with the physiological pregnancy (83 - in the I trimester, 78 - in the II trimester and 109 - in the III trimester) aged from 18 till 44 years with no LUTS before the current pregnancy were examined. LUTS are revealed at 81.9±2.3% of pregnant women. The most common LUTS during pregnancy were: urine incontience, urgency, frequency and nocturia. There was a significantly higher prevalence of storage, voiding and post micturition symptoms with gestational age. Stress urinary incontinence is more often in the multiparous women; nocturia, urgency and frequency are identical in nulliparous and multiparous women. Stress urinary incontinence is more common after vaginal delivery but prevalence rates of nocturia, urgency and frequency do not depend on delivery method.